Early Diagnosis of Pseudohypoparathyroidism before the Development of Hypocalcemia in a Young Infant - Su Kyeong Hwang; Ye Jee Shim; Seung Hwan Oh; Kyung Mi Jang (MDPI AG, 2022)
Pseudohypoparathyroidism (PHP) is a rare, heterogeneous disorder characterized by end-organ resistance to parathyroid hormone (PTH). PTH resistance causes elevated PTH levels, hypocalcemia, and hyperphosphatemia. Since hypocalcemia causes life-threatening events, early diagnosis is crucial. However, the diagnosis of PHP is elusive during infancy because PHP is usually diagnosed with hypocalcemia-induced symptoms, which develop later in childhood when calcium requirements increase. A 1-month-old girl was referred to our clinic for elevated thyroid-stimulating hormone (TSH) levels on newborn screening. When measured 1 month after levothyroxine treatment, her TSH level normalized. At 4-months-old, multiple hard nodules were noted on her trunk. A punch skin biopsy revealed osteoma cutis associated with Albright's hereditary osteodystrophy, a major characteristic of PHP. We performed targeted sanger sequencing of the GNAS gene and detected a heterozygous variant c.150dupA (p.Ser51Ilefs*3) in both the proband and her mother, causing frameshift and premature termination mutations. The patient was diagnosed with PHP Ia when she had normal calcium, phosphorous, and PTH levels. We report the early diagnosis of PHP Ia without hypocalcemia. It emphasizes the importance of meticulous physical examination in patients with congenital hypothyroidism.